Evaluating of Street and Building Ratio as a Criteria of Urban Resilience - Ardicoglu, Ruya (Afet ve Acil Durum Yonetimi Baskanligi (AFAD), 2024)
The aim of the study is considering ratio of building height and street width as resilience criteria and determining risk levels of selected areas by evaluating them in this context. In the study, analyzing areas that is not resilient within the scope of road / building variables and developing suggestions by risk level data in the city of Elazi? that has recently experienced three major earthquakes. It was observed that building and road ratio of existing physical pattern and pattern that will be formed in future do not comply with the regulations and ideal value range of building/road ratios. According to risk rate findings; risk level increases with the new urban plan. The study indicates that, the ratio of building height and street width is important criteria for producing environments where urban fragility is reduced in urban planning and design. The scope of evaluation can be expanded by combining these criteria with other topics and different criterion groups related to urban resilience. © 2024 Afet ve Acil Durum Yonetimi Baskanligi (AFAD). All rights reserved.
Yol ve Bina Oranlarinin Kentsel Dirençlilik Ölçütü Olarak De?erlendirilmesi
Keywords: Decreasing disaster risk; Resistant city; Urban design; Urban planning; Urban resilience